Sparkling Rose Wedding Boutique / Yuhaniza Md. Yusof ... [et al.] - Md. Yusof, Yuhaniza; Karim, Rafidah; Zakaria, Norhayarti; Ishak, Normala; Ali, Norafidah (Faculty of Hotel and Tourism Management, 2002)
Sparkling Rose Wedding Boutique is company of five members. The partners are Yuhaniza Bt. Md. Yusof, Normala Bt. Ishak, Norhayarti Bt. Zakaria, Norafidah Bt. Ali and Rafidah Karim. We choose this name because sparkling means as a love. The aroma of the rose describes a combination of two hearts and will sparkle the couple life forever. The nature of our business is to provide interesting wedding packages and photo session on or off studio from our professional photographer for to be bridal. Putrajaya has great potential as a business center . The location is a new population area created by our government where the area is around 4499 hectors. That is why the government is trying th best to promote this area to the foreign, local tourist especially nearby community.